The Island's Call for Justice: NGO Advocacy in the Climate Litigation Case of Pari Island in Indonesia - Mayaputri, Anya; Gracia Paramitha,; Nurul Isnaeni, (Technium Social Sciences Journal, 2024)
Climate injustice has become a prominent issue following the Paris Agreement, where emissions generated by developed countries burden local communities in developing countries. Consequently, one of the efforts to address climate injustice for communities in the Global South is through climate litigation processes. The process itself is a challenging one since the litigants need support legally and politically to ensure it has proceeded. Here, non-governmental organisation’s (NGO) engagement is the most feasible support that local communities can access. This article analyzes the dynamics of climate justice attempts through a unique case study: climate litigation between residents of Pulau Pari, a small island located in the Java Sea, Indonesia, and the cement giant Holcim-LaFarge in Switzerland. This climate litigation is advocated by three collaborating NGOs: HEKS (Switzerland), ECCHR (Germany), and WALHI (Indonesia). Using a qualitative method, we analyze the role of NGO advocacy in the litigation process using the advocacy function concept by Joseph Szarka; issue framing, construction and dissemination of knowledge, responsibility attribution, political lobbying, public mobilization and agenda setting. We argue that the advocacy support of the three related NGOs amplified the climate litigation process beyond legal proceedings. The strategy of advocating climate litigation is an innovative way to create wider recognition from the international community and push adaptation to the struggle of the local community.